A simple formula for quad mesh singularities. (2017) - Fogg, Harold J.; Sun, Liang; Makem, Jonathan E.; Armstrong, Cecil G.; Robinson, Trevor T.
Abstract: A formula is presented for determining the net sum of mesh singularity indices that must occur in an all-quadrilateral (quad) mesh of a face or surface region after the mesh properties have been assigned on the face's boundaries and according to the face's Euler Characteristic. The formula is derived from Bunin's Continuum Theory for Unstructured Mesh Generation [1].